Nutritional composition of Cassava (Manihot esculenta) and its application to elder-friendly food based on enzyme treatment - Dah-Sol Kim; Fumiko Iida (International Journal of Food Properties, 2023)
Cassava (Manihotesculenta) is known as one of the most nutritious root vegetables, but the texture is relatively hard and tough for the elderly, making it difficult to eat. So, this study attempted to identify the nutritional properties of Cassava and the change in texture according to enzyme treatment to confirm the possibility of using Cassava as anelder-friendly food suitable for the Korean Industrial Standard (KS).To this, the nutritional composition and physiological activity wereanalyzed, and the effect of enzymes (cellulase, polygalacturonase,and α-amylase) on the texture properties of Cassavas was studied. Asa result, Cassava contained various bioactive nutrients such asminerals, essential fatty acids, antioxidants, and anti-diabetessubstances. In all experimental groups, hardness was significantly decreased as the enzyme treatment time increased. Based on KS, when Cassava was treated with cellulase + α-amylase for 3.07 h, α-amylase + polygalacturonase for 3.69 h, and polygalacturonase + cellulase for 4.06 h or more, it showed soft hardness that could be chewed with theelderly's tongue. In addition, it was observed that the microstructure changed as the shape of the tissue was deformed, arrangement became irregular, and size and number of pores increased. In conclusion, root vegetables such as Cassava can be softened tosuit KS using enzymes to promote consumption of elderly consumers andhelp balance nutrition. In addition, considering that Korea isentering a super-aged society, it is thought that this study canprovide positive help to the development of the elder-friendly food industry.